An Overview of Regulatory Guidelines for Medical Gases - Raju, K. Venkateswara (Asian Journal of Pharmaceutics (AJP), 2023)
Direct administration or supply of medical gases to patients is dangeous. Regulatory guidance requirements of various regulatory agencies, the highest quality should be used in their manufacture and transfer. The manufacturer of medical gases requires a license or regulatory approval to manufacture the gases; thus, they must maintain the quality of the gases in accordance with standards or quality limitations established by the drug regulatory authorities. Medicinal gases are manufactured, packed, and designed for patient administration during anesthesia, therapy, or diagnostics. Oxygen, helium, carbon dioxide, nitrous oxide, medicinal air, and nitrogen are officially recognized therapeutic gases. These gases are usually administered preoperatively, intraoperatively, and postoperatively in surgical patients. This gas ignites supplied in an airtight, color-coded, and properly labeled container as required by the relevant regulatory authorities in each country or through the central line runs all over the hospital. Despite all the rules, they are reports on problems related to the production and use of medical gases. In this study, we tried to give a brief overview of regulatory guidelines for medical gases in India and USA.